Bunga Melati Sebagai Elemen Dekoratif Pada Busana Perempuan Dengan Teknik Makrame - Guslina Guslina; Siti Aisyah (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
The jasmine flower, as the symbol of the national flower, holds the meaning of purity and sanctity for several customs and cultures in most parts of Indonesia. The technique used by the author in creating this final work is makrame and sewing techniques in the form of women's fashion. The sanctity of the jasmine flower became the inspiration for the author to create craft art in the form of makrame, while also introducing and realizing the creative idea of textile makrame craft art more widely to the public. Women's clothing with jasmine flower motifs using makrame techniques aims to educate the public more broadly about how makrame craft art can be translated into creative artistic ideas and even serve as a medium for social criticism. The method used by the author in creating this work includes: Preparation, elaboration, synthesis, realization of the concept, and completion. The results achieved in creating this makrame work are titled: Qurrota a’yun (Soothing to the Heart), Izzah (Purity and Nobility), Iffah (Sense of Modesty), Al-husn (True Beauty), Madrasatul ‘ula (The First School), Hawadah (Gentleness), Muhubbun Rahim (Loving and Compassionate).